United Arab Emirates : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report ;, 2006)
An outward-oriented development strategy and prudent financial policies resulted in an impressive economic growth and led to a large accumulation of external financial assets. The major Emirates intend to leverage the favorable economic environment to carry out reforms that will encourage more private sector participation. Owing to the complexities of interlinkages between financial and real sectors, broad and proper information is needed to allow comprehensive economic development. As a result of deficient data, significant constraints on economic monitoring, analysis, and policy formulation are imposed.